Eco-friendly synthesis of gold nanoparticles via tangerine peel extract: Unveiling their multifaceted biological and catalytic potentials - Seyedeh Masoumeh Ghoreishi; Sobhan Mortazavi-Derazkola (Heliyon)
Recent advancements in nanoscience underscore the transformative potential of nanomaterials in environmental and biological applications. In this study, we synthesized gold nanoparticles (Au@TPE NPs) using an eco-friendly and cost-effective approach, leveraging tangerine peel extract as both a capping and reducing agent. This method presents a sustainable alternative to traditional chemical agents. We optimized synthesis parameters, including time (5, 30, 60, and 90 min), temperature (25, 40, and 60 °C), and gold concentration (5, 10, 15, and 20 mM) to refine the nanoparticles size and morphology. Characterization via UV–Vis, XRD, FT-IR, EDAX, FESEM, and TEM revealed that nanoparticles synthesized at 40 °C and 15 mM gold concentration exhibited an optimal size (∼26 ± 5 nm) and a spherical shape. The Au@TPE NPs demonstrated antibacterial activity against both Gram-positive and Gram-negative bacteria, with minimum inhibitory concentrations (MIC) of 31.25 μg/ml for Klebsiella pneumoniae and Escherichia coli, and 62.5 μg/ml for Pseudomonas aeruginosa. Notably, they also exhibited antifungal activity against Candida albicans and demonstrated 92.7 % antioxidant activity in a DPPH scavenging assay at 250 μg/ml. Photocatalytic tests revealed that the nanoparticles effectively degraded methyl orange and rhodamine B, achieving 88.6 % and 93.2 % degradation under UV light, respectively, and 67.3 % and 74.1 % degradation under sunlight. These promising biological and catalytic properties suggest significant potential for diverse applications.